Gastric Ulcer Hemorrhage - a Potential Life-Threatening Complication of Intragastric Balloon Treatment of Obesity - Aleksandra Mojkowska; Stefan Gazdzinski; Mariusz Fraczek; Mariusz Wyleżoł (Obesity Facts, 2017)
Background: Some morbidly obese patients do not qualify for bariatric surgery due to general health contraindications. Intragastric balloon treatment might be a therapeutic option in the above-mentioned cases. It can prime super-obese patients with end-stage disease for bariatric surgery. As a neoadjuvant therapy before surgery, it leads to a downstage of the disease by preliminary weight reduction, to an improvement in general health and, in summary, to a reduction of the perioperative risk. It is generally considered to be a safe method. However, due to the wide range of possible complications and unusual symptoms after intragastric balloon treatment, an interdisciplinary, instead of only a surgical or endoscopic, treatment and follow-up might be recommended in these patients. Case Report: We here describe a potential life-threatening complication in the form of gastric bleeding as a consequence of intragastric balloon treatment and simultaneous aspirin taking and Helicobacter pylori infection. Conclusion: There have been reports of some complications of intragastric balloon treatment. However, to the best of our knowledge there were no reports concerning life-threatening hemorrhage from gastric ulcer.